Trachoma in the Sudan. A laboratory study. - Salim, A R (1975)
Out of 46 patients in the Sudan who had been diagnosed clinically as having trachoma 25 strains of the trachoma agent were isolated. Bacterial contamination was easily controlled by streptomycin and vancomycin. On repeated passaging, chick embryos lost their susceptibility to the trachoma agent during the summer.